Sistema de monitoramento remoto online de sinais cardíacos via rede GPRS - Vargas, Ricardo Emanuel Vaz (2008)
Nowadays heart diseases are considered the main cause of death and limiting and final injuries that happens in several times at early age. The ECG examination is considered by the specialists the default procedure to diagnose this type of disease. It is cheap, non-invasive, and necessary to diagnose many arrhythmias of the heart. Therefore, the ECG monitoring may mean the difference between death and life of several patients. The goal of this thesis was to develop a solution of remote, continuous and online ECG monitoring based on GPRS technology. This technology has been used in this kind of system and it presents excellent features: connections are always kept active; the rate is based on the volume of transferred data; and its covered area is large. The presented solution is composed of mobile devices, kept by patients, that capture 3 ECG leads and send them, through a GPRS network, to a server installed in a health institution. Before the transmission, a mobile device filters, amplifies and converts to digital the signals that have been captured. A server receives the transmissions from many mobile devices and save all ECG information in a data base. A Web interface can provide this information on the Internet. As any open communication protocol, suitable to the proposed solution, has not been found an application protocol called PMR was developed also. It has shown itself flexible and useful to applications that need to transfer information of analog signals in general, not just signals related to telemedicine. A prototype including hardware and software was developed to allow an assessment of the performance of the presented solution. Several parameters that can measure the quality of the proposal were monitored and the obtained results show that the solution is feasible.